Bentuk dan Penyimpangan Penggunaan Youjigo dalam Anime Mirai Karya Mamoru Hosoda - Putri Kinanti, I Gusti Agung Ayu; Dewi, Ni Made Andry Anita; Sari, Ida Ayu Laksmita (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023), 2023)
This research is entitled as Bentuk dan Penyimpangan Penggunaan Youjigo Dalam Anime Mirai Karya Mamoru Hosoda. This research was made to find out the form of use and usage deviation of youjigo in anime Mirai by Mamoru Hosoda. The method that used in this research is qualitative descriptive method. Yakuwarigo theory’s by Kinsui (2003) which helped by Okazaki (2010) about youjigo ’s characteristics and Tarou (1975) about youjigo ’s suffixes form is used to identify the form of use of youjigo in anime Mirai. Meanwhile, SPEAKING theory by Hymes (1972) is used to identify the usage deviation of youjigo in anime Mirai. Data source of this research is qualitative data such as dialogues and monologues from characters Kun, ibu ketika masih kecil, and ayah. The result of this research found that the form of use of youjigo in anime Mirai is omission, dropping o and ga particles, and suffixes - no ,  - yo , - no ne , - yo ne , and - mon . Afterwards, the usage deviation of anime Mirai was used by ayah when speaking with Kun. Usage deviation of youjigo was used to facilitate the delivery of information to children.